2016
DOI: 10.1088/1612-2011/13/9/095003
|View full text |Cite
|
Sign up to set email alerts
|

15 mJ single-frequency Ho:YAG laser resonantly pumped by a 1.9µm laser diode

Abstract: A 2.09 µm injection-seeded single-frequency Ho:YAG laser resonantly pumped by a 1.91 µm laser diode is demonstrated for the first time. The seed laser is a continuous wave (CW) Ho:YAG non-planar ring oscillator. 15.15 mJ single-frequency output energy is obtained from the injection-seeded Q-switched Ho:YAG laser, with a pulse repetition rate of 200 Hz and a pulse width of 109 ns. The half-width of the pulse spectrum is measured to be 4.19 MHz by using the heterodyne technique. The fluctuation of the center fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A maximum single-frequency pulsed energy of 15.15 mJ for 109 ns pulse width at 200 Hz was realized. 20 Next, they reported a Ho:YAG injection-locked Q-switching laser delivering a pulse energy of 9.7 mJ, corresponding to a 183 ns pulse duration at 252 Hz. 21 To meet the requirements of a lidar system for 2.09 μm single-frequency pulsed laser sources with high energy, an effective method of oscillator-amplifier system 22 is generally adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A maximum single-frequency pulsed energy of 15.15 mJ for 109 ns pulse width at 200 Hz was realized. 20 Next, they reported a Ho:YAG injection-locked Q-switching laser delivering a pulse energy of 9.7 mJ, corresponding to a 183 ns pulse duration at 252 Hz. 21 To meet the requirements of a lidar system for 2.09 μm single-frequency pulsed laser sources with high energy, an effective method of oscillator-amplifier system 22 is generally adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Na et al demonstrated a 2.09 μm injection‐locked Q‐switched Ho:YAG oscillator, which was pumped by a 1.91 μm laser diode. A maximum single‐frequency pulsed energy of 15.15 mJ for 109 ns pulse width at 200 Hz was realized 20 . Next, they reported a Ho:YAG injection‐locked Q‐switching laser delivering a pulse energy of 9.7 mJ, corresponding to a 183 ns pulse duration at 252 Hz 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, they replaced the seed laser with a Ho:YAG nonplanar ring oscillator (NPRO) and obtained an output energy of 11 mJ at repetition rate of 110 Hz [5,6]. In 2016, we reported a 15 mJ single-frequency Ho:YAG laser, where the seed was injected by an acoustic-optical (AO) Q-switcher [7].…”
Section: Introductionmentioning
confidence: 99%
“…10,11) Na et al developed single-frequency lasers with both Ho:YAG crystal and ceramics generating pulses of about 15 mJ at a PRF of 200 Hz. 12,13) In a wind measurement lidar system, high pulse energy and PRF means high speed to scan a whole wind field, 14) which is very important, especially for precise wind speed measurement in airports. Here, we report an injection-seeded, PRF changeable single-frequency Ho:YAG laser with PRF changing from 150 to 750 Hz, which is the highest PRF ever obtained in a Ho:YAG single-frequency laser.…”
mentioning
confidence: 99%